2019
DOI: 10.1007/s12144-019-00192-2
|View full text |Cite
|
Sign up to set email alerts
|

The Polish adaptation and further validation of the Fear of Being Single Scale (FBSS)

Abstract: The article discusses the results of the validation and psychometric parameters of the Polish-language version of the Fear of Being Single Scale (FBSS), originally developed by Spielmann and colleagues (2013). The study participants included 175 Polish respondents aged 18 to 67 (M = 27.19, SD = 8.63). The findings confirmed the one-dimensional structure of the Polish FBSS, convergent, discriminant and concurrent validity, reliability of the Polish FBSS, and its high test–retest reliability over a lag of six mo… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

0
11
0
2

Year Published

2019
2019
2024
2024

Publication Types

Select...
7
1
1

Relationship

0
9

Authors

Journals

citations
Cited by 12 publications
(13 citation statements)
references
References 23 publications
0
11
0
2
Order By: Relevance
“…We expected to obtain a reliable and valid tool. To examine the divergent validity, we employed the variables (i.e., generalized anxiety, attachment anxiety, and personality traits) in parallel with the previous studies (Adamczyk et al, 2021;Fonseca et al, 2017;Spielmann et al, 2013). To test the convergent validity, we used two additional variables (i.e., the need to belong and the inclusion of others into self).…”
Section: The Current Studymentioning
confidence: 99%
“…We expected to obtain a reliable and valid tool. To examine the divergent validity, we employed the variables (i.e., generalized anxiety, attachment anxiety, and personality traits) in parallel with the previous studies (Adamczyk et al, 2021;Fonseca et al, 2017;Spielmann et al, 2013). To test the convergent validity, we used two additional variables (i.e., the need to belong and the inclusion of others into self).…”
Section: The Current Studymentioning
confidence: 99%
“…V praxi se zohlednění strachu být nezadaný jeví být užitečné pro lepší pochopení vztahových postojů a chování. Na základě dosavadního výzkumu byla prokázána jeho pozitivní souvislost s dalšími konstrukty interpersonální senzitivity jako například citlivost k odmítnutí (rejection sensitivity), náchylnost k pocitům ublíženosti (hurt feelings proneness), vztahem podmíněné sebehodnocení (relationship-contingent self-esteem), deprese (depression), potřeba sounáležitosti (need to belong) či osamělost (loneliness), ať už ve smyslu sociální, tak emoční, či specificky romantické osamělosti (romantic loneliness) (Adamczyk, 2018;Adamczyk et al, 2019;da Fonseca et al, 2017;Spielmann et al, 2013). Obecně jedinci s intenzivnějšími obavami o svůj vztahový status mají v rámci sociálního kontaktu sklon se spíše zaměřit na vyhýbání se negativním důsledkům (social avoidance goals) než na dosahování pozitivních cílů (social approach goals) (Spielmann et al, 2013).…”
Section: Teoretická Východiskaunclassified
“…Spielmann et al (2013) developed a six-item scale to measure the construct, with such items as, "As I get older, it will become harder and harder to find someone." The scale has been shown to have excellent validity and reliability (Adamczyk et al, 2021;Fonseca, Gouveia, Santos, Couto, & Coelho, 2017;Spielmann et al, 2013), and is associated with, but distinct from, other psychological dispositions such as attachment anxiety (Spielmann et al, 2013;Spielmann, Maxwell, MacDonald, Peragine, & Impett, 2020). Young women may be especially prone to FOBS for the same cultural, normative, biological, and structural reasons discussed above that could lead members of their close ties to push them to find a partner.…”
Section: Fear Of Being Singlementioning
confidence: 99%
“…Young women may be especially prone to FOBS for the same cultural, normative, biological, and structural reasons discussed above that could lead members of their close ties to push them to find a partner. Some past research has found that women score higher than men on FOBS (e.g., Adamczyk, 2018;Adamczyk et al, 2021).…”
Section: Fear Of Being Singlementioning
confidence: 99%